Kedudukan Dan Peran Mahasiswa Dalam Masyarakat Multikultural Di Politeknik Negeri Ambon - Ohorella, Sapia Ainun; Abdin, Maslan; Saptenno, Agustina; Patrouw, Inda Mauren; Nurilhaq, Nu'man Sadidan (Scholars: Jurnal Sosial Humaniora dan Pendidikan, 2023)
The lack of knowledge, awareness and attitudes is an indicator of weakening multiculturalism. If allowed to drag on, it can trigger both vertical and horizontal conflicts in Indonesia. Ambon State Polytechnic students are a multicultural society, this can be seen from the diversity of ethnicity, religion, race and culture of the student community. If this diversity is not accepted or implemented properly, it can result in conflicts related to SARA, and even lead to racism between peers or groups among Ambon State Polytechnic students. This research aims to find out how the practice of multiculturalism towards multicultural communities at the Ambon State Polytechnic. The method approach in this research is mixing methods which are carried out using qualitative methods (direct interviews) and quantitative methods (numbers). The results of the research showed that the level of understanding of Ambon State Polytechnic students was around 53% of students VERY UNDERSTANDING the meaning and position of students and around 47% UNDERSTANDING this. This is reinforced by the results of interviews. Furthermore, student attitudes towards diversity at Polnam showed VERY GOOD 58%; GOOD 22%; and PRETTY GOOD 20%. This is also confirmed by the results of interviews from the 5th. And if we look at the implementation of multiculturalism at POLNAM, 93% of POLNAM students have practiced multiculturalism, while around 7% of students have not implemented a multiculturalism attitude.Keywords: conflict, multicultural society, multiculturalism